Teaching strategies employed by selected ESL writing teachers in the Klang Valley, Malaysia - Zakaria, Noraizzah (2013)
The main purpose of this study was to investigate the situational context in selected ESL writing classrooms in Klang district, Selangor DarulEhsan. These teaching strategies employed by teachers are significant in teaching writing in the Malaysian context with the hope that by the end of eleven years in learning English, students would be able to write essay with confidence according to the required standard. This study was carried out through the detailed investigation of three research questions. They include: (1) What are the strategies used by teachers in ESL writing classrooms? (2) How do the strategies employed by teachers differ in high achievers’ and low achievers’ classrooms (3) What factors contribute to the teaching strategies used in teaching composition writing to ESL learners? These questions were vigorously addressed throughout the study with the specific concern of determining their relations to strategies employed by teachers in ESL writing classrooms. The qualitative case study research methodology was selected since it was deemed the most appropriate for the study of this nature. Data were gathered and generated from seven ESL teachers in government schools. The participants were selected from teachers who were willing to participate in this study with more than five years experience in teaching English. The data collection method employed to achieve the purpose of this study were mainly classroom observations, and in depth interviews with the participants. Each observation lasted between one hour to about one and a half hours, was taped recorded, transcribed verbatim and analyzed according to different types of teaching strategies. The interviews were also interviewed to verify the data based on observations in the classrooms. Thematic analysis was used to derive themes from the data. The rigor and trustworthiness of the study were further ensured through member checks, peer examination and maintenance of an audit trail. The findings yielded the various strategies in teaching writing namely; memory strategies, cognitive strategies, compensation strategies, meta-cognitive strategies, affective strategies and social strategies. Strategies used by teachers in high achievers’ classrooms were also used by teachers in low achievers’ classrooms and vice versa. The teacher-factor and student-factor were salient in this study. Teachers are recommended to use teaching strategies that will provide favourable input which will lead to student-centred environment in the classrooms. Specific recommendations for further research were also suggested.